2018
DOI: 10.31234/osf.io/gncsp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations Between Unintended Pregnancy, Domestic Violence, and Sexual Assault in a population of Queensland Women

Abstract: This study aimed to establish the proportion of women seeking information regarding unintended pregnancy in the context of domestic violence (DV) and/or sexual assault (SA) experiences in Queensland. Mental health, sociodemographic variables, and gestation at first and repeated contacts were examined for 6249 women primarily seeking information regarding abortion options during an unintended pregnancy over the five-year period from July 2012 to June 2017. Reports of DV and SA and associations with mental healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Further, this documentation may alleviate some patient experiences where they report difficulty accessing health workers who understand the potential severity of NFS and receiving referrals for scans or social work support. 47 …”
Section: Discussionmentioning
confidence: 99%
“…Further, this documentation may alleviate some patient experiences where they report difficulty accessing health workers who understand the potential severity of NFS and receiving referrals for scans or social work support. 47 …”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, mental health problems, illicit drugs use and binge drinking have been associated with unplanned pregnancy [ 21 , 23 , 24 ]. Finally, sexual violence, intimate partner violence and coercion are associated with unplanned pregnancy [ 25 ]. Five to 7 % of the women who experienced rape reported that they got pregnant as a result of the rape [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reproductive health is particularly threatened since violent partners may force sexual intercourse, refuse to use contraception during intercourse, and restrict women's access to healthcare facilities (Miller et al., 2010). Women victims‐survivors of IPV are more likely to seek abortions (Coker, 2007; Fanslow et al., 2008), to contract sexually transmitted infections (STIs), to suffer sexual trauma and to develop pelvic inflammatory disease than non‐abused women (Hunter et al., 2017; Sharman et al., 2018). In addition, female survivors of violence have a higher prevalence of anxiety disorders (Trevillion et al., 2012), sleep disorders (Pengpid & Peltzer, 2020), depression (Beydoun et al., 1982) and post‐traumatic stress disorder (PTSD) (Husky et al., 2015; Jaspard et al., 2001; McCauley et al., 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Reproductive health is particularly threatened since violent partners may force sexual intercourse, refuse to use contraception during intercourse, and restrict women's access to healthcare facilities (Miller et al, 2010). Women victims-survivors of IPV are more likely to seek abortions (Coker, 2007;Fanslow et al, 2008), to contract sexually transmitted infections (STIs), to suffer sexual trauma and to develop pelvic inflammatory disease than non-abused women (Hunter et al, 2017;Sharman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%